Genetic Diversity Recent Advances and Applications - Çalişkan, Mahmut; Aydin, Sevcan (IntechOpen, 2023)
This book covers the dynamic process of genetic diversity in living organisms. It comprises eight chapters that address various topics, including genetic diversity in crop production, the relationship between viruses and their hosts, patterns of genetic variability in silver carp populations in Pakistan, molecular markers used for wildlife conservation, and more.